Development of Tahfidz Learning Method Selected Letters with Flash-Qu Media (Qur'an Flashcard) - Rahman, Zidan Kurnia; Nurrohim, Ahmad; Alhafidz, Alviola Daffa (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The education provided in mi survivors of media use using student presentations and package books using a talk method without variation and using less of the media use in explaining the lesson materials. This can lower students' interest in learning, students become less enthusiastic so that materials presented less understood need a medium capable of attracting and enthusiastic students in the process of learning in order to reproduce the material presented so that the results can increase. One of the media that is capable of attracting and enthusiastic students to the right process for learning to increase focus and can understand material that is presented is the it lash card of the media flash card visa medium that contains a simple media study material that is very easy to create, doesn't require special skill, so anyone can create it. Flash card understanding according to Azhar Arsyad (2011:119) flash card is a small card with a reminder picture, text, or symbol mark for leading students to something related to the picture. Flash-Qu method employed for learning Tahfidz Juz 30, focusing on enhancing children's memory retention. The use of these Flash-Qu is motivated by the friendly nature of the media, specifically designed for children, especially those in primary school, aiming to provide a perception to children that memorization is not difficult but enjoyable. With these Flash-Qu, children can master each verse of selected surahs, not only the recitation but also the verse number and its meaning. The use of Flash-Qu can sharpen children's memory due to the inclusion of illustrations, making it an engaging tool for both memorization and revisiting the memorized content.